Experimental and theoretical investigations into the stability of cyclic aminals - Sawatzky, Edgar; Drakopoulos, Antonios; Rölz, Martin; Sotriffer, Christoph; Engels, Bernd; Decker, Michael (Beilstein Journal of Organic Chemistry, 2016)
Background: Cyclic aminals are core features of natural products, drug molecules and important synthetic intermediates. Despite their relevance, systematic investigations into their stability towards hydrolysis depending on the pH value are lacking.Results: A set of cyclic aminals was synthesized and their stability quantified by kinetic measurements. Steric and electronic effects were investigated by choosing appropriate groups. Both molecular mechanics (MM) and density functional theory (DFT) based studies were applied to support and explain the results obtained. Rapid decomposition is observed in acidic aqueous media for all cyclic aminals which occurs as a reversible reaction. Electronic effects do not seem relevant with regard to stability, but the magnitude of the conformational energy of the ring system and pKa values of the N-3 nitrogen atom.Conclusion: Cyclic aminals are stable compounds when not exposed to acidic media and their stability is mainly dependent on the conformational energy of the ring system. Therefore, for the preparation and work-up of these valuable synthetic intermediates and natural products, appropriate conditions have to be chosen and for application as drug molecules their sensitivity towards hydrolysis has to be taken into account.
Keywords: hydrolysis; kinetics; molecular mechanics; natural products; quantum mechanics